PERK/eIF2α pathway affected the thyroid hormone synthetic in hypertensive disorders of pregnancy rats - Wu, Congrong; Sun, Maomao; He, Yue; Jiang, Jie; Wang, Luran; Wang, Yanni; Yu, Yonghui (Frontiers in Endocrinology, 2025)
BackgroundClinical research has identified a correlation between hypertensive disorders of pregnancy (HDP) and subclinical hypothyroidism during gestation. But the potential influence of HDP on thyroid hormone synthesis remains undetermined.AimsThis study aims to elucidate the impact of HDP on thyroid hormone synthesis and to delineate the underlying mechanisms.Methods20 pregnancy SD rats were stratified at random into the HDP group and the Control group. The HDP group was subjected to NG-Nitro-L-arginine-methylester administration from gestational days 13 to 20, while the Control group received saline. Subsequent assessments encompassed serum FT4, FT3, and TSH concentrations, morphological examination of the thyroid, as well as quantification of essential proteins pivotal to thyroid hormone synthesis and markers indicative of endoplasmic reticulum stress.ResultsThe HDP group exhibited a statistically significant augmentation in serum TSH concentrations (p<0.05), while FT3 and FT4 levels manifested no discernible statistical variations. H&E staining highlighted a pronounced hyperplasia of the follicular epithelial cells and a diminution in the follicle lumen area. Electron microscopy unveiled pronounced endoplasmic reticulum markedly swelling and expansion within the HDP group. Molecular evaluations revealed a decrement in Tg expression within thyroid tissue, concomitant with an upregulated expression of p-PERK, P-eIF2α, and ATF4.ConclusionThis investigation suggests that HDP might modulate Tg expression within thyroid tissue, possibly mediated through the PERK/eIF2α signaling cascade. This perturbation may compromise thyroid hormone synthesis, thereby predisposing pregnant rats to subclinical hypothyroidism.